Thoracic Epidural Catheter Placement in a Preoperative Block Area Improves Operating Room Efficiency and Decreases Epidural Failure Rate. Issue 5 (September 2017) - Gleicher, Yehoshua; Singer, Oskar; Choi, Stephen; McHardy, Paul
Abstract : Background and Objectives: The primary aim of this study was to review the impact of inserting thoracic epidural catheters in a preoperative block room setting on operating room efficiency. Methods: We conducted a retrospective preintervention/postintervention review of thoracic epidurals inserted over a 12-month period. The review included 6 months of data prior to implementation of the regional anesthesia block room and 6 months of data following implementation. The primary outcome measure was anesthesia-controlled operating room time, defined as time from patient arrival to the operating room to time of surgical site sterile preparation. Secondary measures included operating room waiting time for the patient arrival, thoracic epidural failure rate, and number of epidural insertion attempts. Results: Data from thoracic epidurals for 112 patients of preblock room and 142 patients of postblock room implementation were collected. Anesthesia-controlled operating room time was reduced by an average of 22.9 minutes per patient (95% confidence interval, 19.3–26.3 minutes; P < 0.01). Average operating room waiting time for patient arrival increased by 3.8 minutes (95% confidence interval, 1.0–6.5 minutes; P < 0.01), resulting in net operating room time savings of 19.1 minutes per epidural. The epidural failure rate decreased from 16.0% to 5.6% ( P < 0.01). There was no difference in the number of epidural insertion attempts made per patient. Conclusions: Insertion of thoracic epidural analgesia in a preoperative block room setting can significantly reduce anesthesia-controlled operating room time and epidural failure rates.